Brucellar epididymo-orchitis in southeastern part of Turkey: an 8 year experience - Mustafa Kemal Celen (Brazilian Journal of Infectious Diseases)
OBJECTIVE: the different clinical and laboratory features and response to treatment of patients with acute brucellar epididymo-orchitis (BEO) reporting to the reference hospital in Southeastern Anatolia of Turkey. MATERIAL AND METHODS: in this study, 27 male patients with brucellosis, who presented with epididymitis or epididymo-orchitis (EO) at the university hospital in Diyarbakir from 1998 to 2006, were included. They were compared with the other male patients. Positive blood culture or high agglutination titers of > 1/160 and positive clinical manifestations of brucellosis were the main criteria for diagnosing brucellosis. RESULTS: fourteen patients had unilateral EO. Leukocytosis was present in 10 patients; all of them had initial agglutination titers of > 1/160 and 10 patients had a positive blood culture. All patients received combined therapy with streptomycin for the first 21 days (or oral rifampicin for 6-8 weeks) with doxycycline or tetracycline for 6-8 weeks. All showed improvement, fever subsided in 3-7 days, and the scrotal enlargement and tenderness regressed. Only one patient had a relapse within one year. CONCLUSION: in brucellosis-endemic areas, clinicians encountering EO should consider the likelihood of brucellosis. In this study, young age was the most common risk factor, and leukocytosis and high CRP level were the most common laboratory findings. Most cases were unilateral. All patients responded to medical management very well. Conservative management with combination antibiotic therapy was adequate for managing BEO. Conclusively, brucellosis must be considered as a cause of orchitis, especially in endemic regions like Turkey.